Obstruction from Deflux leading to significant kidney function loss and chemotherapeutic challenges in pediatric Ewing sarcoma - Luke Martin; Dipen Mehta; Bradley Morganstern (Urology Case Reports)
This report presents the case of an 8-year-old female with a history of vesicoureteral reflux (VUR) treated with Deflux injections, who developed Ewing sarcoma metastasized to the lungs. Despite the initial resolution of VUR following Deflux procedures, recurrent urinary tract infections prompted further evaluation revealing significant ureteral obstruction. Pre-chemotherapy workup included renal ultrasonography, nuclear medicine renal scan, and cystogram, identifying obstructive uropathy necessitating bilateral ureteral stent placement. This discussion encompasses the challenges of managing VUR, Deflux complications, and the importance of tailored follow-up protocols.